Wealth inequality and the distributional effects of maximum loan-to-value ratio policy - William Gatt (Central Bank of Malta, 2023)
Macroprudential policy improves economic outcomes by reducing the likelihood and severity of financial crises. Yet it is pertinent to ask, are there unintended long run consequences to the introduction of a macroprudential policy regime, and are these consequences conditional on the a priori level of wealth inequality? This paper answers these questions by looking at the effect of a reduction in the maximum loan-to-value (LTV) ratio on homeownership rates, house prices and housing wealth inequality across two economies with different initial wealth dispersion. It uses a heterogeneous agent model in which households face uninsurable income risk and an endogenous borrowing limit in the form of a collateral constraint. This constraint is initially loose, allowing households to lever up against the collateral value of their housing. A reduction in the LTV limit tightens the borrowing constraint, and lowers homeownership as a greater share of households no longer afford the downpayment. The key finding of this paper is that initial conditions matter; the lower is wealth inequality ex-ante, the higher is the fall in house prices and the greater is the rise in the share of constrained homeowners and housing wealth inequality ex-post. The effects are also non-linear in the LTV ratio, with progressively stronger effects at lower LTV ratios, especially when inequality is comparatively low.
Keywords: E21; G11; G28; G51; R21; 330; wealth distribution; housing; macroprudential policy; loan-to-value; saving